POLICE (BAKSOS) AS AN ALTERNATIVE TO STRENGTHEN PUBLIC TRUST AMIDST THE CRISIS OF LEGITIMACY OF THE INDONESIAN REPUBLIC POLICE INSTITUTION - Makudali K. Lattu; Gatot Sasongko; Royke R. Siahainenia (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines the role of the police outside the formalization of legal policies through interactive-humanist actions to overcome the crisis of institutional legitimacy of the Indonesian National Police (Polri). This article focuses on social services carried out by Polri members as an alternative to reconstructing public trust amidst the crisis of institutional legitimacy. By reducing various strategic policies and using philanthropic efforts through social services, the police can act humanely and avoid repressive actions to improve the image of the Polri. Social service police can be a new approach in the reconstruction of Police-Community relations that are carried out personally and informally, but still play a role in strengthening public trust in the image of the Polri socially through police-community involvement. By explaining the problems of public distrust and the Polri legitimacy crisis, and referring to the concept of legitimacy and various studies related to police issues, the main argument of this article is that social service police are not just a caricature mechanism or formal institutional policy - but rather a tactical effort based on the reconstruction of public trust to improve the legitimacy crisis due to the fading image of the Polri outside the formal mechanism through a soft power approach . nenwun